Support for a right-wing populist party and subjective well-being: Experimental and survey evidence from Germany - Maja Adena; Steffen Huck (PLOS ONE, 2024)
With the rise of populism in many countries, including Germany, it is more important than ever to better understand the causes and consequences of populist support. Using two experiments within the context of a large panel survey, we study how support for the German right-wing populist party Alternative für Deutschland (AfD) is associated with subjective perceptions of personal and financial well-being. In both experiments, we rely on priming the identity of AfD supporters, once in a controlled manner and once in a natural setting. We document a causal relationship from AfD support to diminished well-being for new and marginal AfD supporters. Our findings challenge the prevailing assumption that causality moves unidirectionally, from life dissatisfaction to support for populist parties, and suggest that early interventions focusing on positive messages are particularly promising to win voters back into the mainstream.
https://doi.org/10.7802/2714
Keywords: 300